2020
DOI: 10.3390/ijms21176272
|View full text |Cite
|
Sign up to set email alerts
|

Tetrapeptide Ac-HAEE-NH2 Protects α4β2 nAChR from Inhibition by Aβ

Abstract: The cholinergic deficit in Alzheimer’s disease (AD) may arise from selective loss of cholinergic neurons caused by the binding of Aβ peptide to nicotinic acetylcholine receptors (nAChRs). Thus, compounds preventing such an interaction are needed to address the cholinergic dysfunction. Recent findings suggest that the 11EVHH14 site in Aβ peptide mediates its interaction with α4β2 nAChR. This site contains several charged amino acid residues, hence we hypothesized that the formation of Aβ-α4β2 nAChR complex is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 84 publications
(161 reference statements)
0
18
0
Order By: Relevance
“…These findings are consistent with earlier evidence showing that a different core Aβ fragment, Aβ 12-28 , that contains the critical residues of the Aβcore is sufficient to prevent Aβ from binding to α7-nAChRs and reverse Aβ-induced inhibition of α7-nAChRs (44). Finally, a recent study shows that the formation of Aβ-α4β2-nAChRs complex is based on the interaction of a part of Aβcore sequence (EVHH) with α4β2-containing receptors, and blocking this interaction prevents Aβ42-induced inhibition of α4β2-nAChRs (45). This thus suggests interrupting the association of Aβ with nAChRs may be neuroprotective against Aβ-induced neuronal dysfunction in AD, although the differential impact of Aβcore on the three major nAChRs in the hippocampus remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with earlier evidence showing that a different core Aβ fragment, Aβ 12-28 , that contains the critical residues of the Aβcore is sufficient to prevent Aβ from binding to α7-nAChRs and reverse Aβ-induced inhibition of α7-nAChRs (44). Finally, a recent study shows that the formation of Aβ-α4β2-nAChRs complex is based on the interaction of a part of Aβcore sequence (EVHH) with α4β2-containing receptors, and blocking this interaction prevents Aβ42-induced inhibition of α4β2-nAChRs (45). This thus suggests interrupting the association of Aβ with nAChRs may be neuroprotective against Aβ-induced neuronal dysfunction in AD, although the differential impact of Aβcore on the three major nAChRs in the hippocampus remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with earlier evidence showing that a different core Aβ fragment, Aβ 12–28 , that contains the critical residues of the Aβcore is sufficient to prevent Aβ from binding to α7-nAChRs and reverse Aβ-induced inhibition of α7-nAChRs ( 44 ). Finally, a recent study shows that the formation of the Aβ–α4β2-nAChRs complex is based on the interaction of a part of Aβcore sequence (EVHH) with α4β2-containing receptors, and blocking this interaction prevents Aβ42-induced inhibition of α4β2-nAChRs ( 45 ). This thus suggests that interrupting the association of Aβ with nAChRs may be neuroprotective against Aβ-induced neuronal dysfunction in AD, although the differential impact of the Aβcore on the three major nAChRs in the hippocampus remains to be explored.…”
mentioning
confidence: 99%
“…Since Aβ accumulates in the brain regions enriched in α4β2 nAChRs and α7 nAChRs, the selective vulnerability of the hippocampus to Aβ toxicity can be associated with the high-affinity interaction between Aβ and these nAChRs [ 33 , 34 , 35 , 36 ]. The Aβ–α4β2 nAChR interaction interface is formed by the 11-EVHH-14 and 35-HAEE-38 sites of Aβ and the α4 subunit of α4β2 nAChR, respectively [ 5 ]. The 11-EVHH-14 region of Aβ also plays a critical role in Aβ binding to α7 nAChRs; however, the exact interface of the Aβ-α7 nAChR complex is unknown [ 4 , 6 , 29 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such interactions can play a pivotal role in the pathogenesis of AD by initiation of the formation of both neurotoxic Aβ oligomers in biological fluids of the body and extracellular insoluble Aβ aggregates in amyloid plaques characteristic of AD [ 2 ]. It was previously shown that the Aβ site 11-EVHH-14 [ 3 , 4 ] and the site 35-HAEE-38 of the α4 subunit of the α4β2 subtype of nicotinic acetylcholine receptors (α4β2 nAChR) [ 5 ] participate in the Aβ-α4β2 nAChR interaction interface. Synthetic analogs of these sites stabilize the monomeric state of Aβ in vitro and are considered as potential anti-amyloid agents for the treatment of AD [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%